KINERJA PEGAWAI DI UNIT PELATIHAN TRANSMIGRASI PROVINSI KALIMANTAN BARAT - Tuti Yuliawati E.21109113 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study the effectiveness of the work produced by the driving NGO has not been fully demonstrated the efficiency of the time because the work has not been supported by adequate means. And placement of non-governmental mover that does not comply with the discipline, which can decrease the performance of governmental mover in areas that will indirectly lower the quality of his work. Problems in this study focused on the drivers of Governmental Performance Measurement masyarakt Transmigration Training Unit. In this study the authors use this type of research deskrptif, which only depict or describe the circumstances in accordance with what is currently the research done, and then analyzed, the data collected is in the form of words, images, and not the numbers. The results showed that the performance of PSM in the Training Unit of West Kalimantan Transmigration is good enough. It is based on six indicators of performance assessments consisting of quality of work, quantity of work, time accuracy, the effectiveness of self-reliance and commitment based on the results of the research work pretty well, although there are still some drivers of Governmental still not able to master the use of various office facilities in supporting the task kelancaraan and work. Further addressing the phenomenon that is to issue the quantity of work that must be optimized in Transmigration Training Unit of West Kalimantan Province is concerned about the ability of Governmental Activator (PSM) to balance the amount of work that must be done diligently and coupled with the Activator Organization (PSM) in the office. Furthermore, given that at any time the performance Activator Organization (PSM) Transmigration Training Unit in West Kalimantan province supervised and assessed by the supervisor, should Mover Organization (PSM) was also noticed in earnest on their own performance. Should be aligned to the performance Activator Organization (PSM) is increased or at least the absence of efforts to maintain excellent performance. And the attitude of the last solution is a custom patterned, if the patterned habits have positive implications in relation to the behavior of one's work it will be profitable. If the habit of Governmental Activator (PSM) well then it can guarantee good work habits as well. So the level of discipline Activator Organization (PSM) needs to be improved further so that it can support a more effective job. Keywords: Measurement, Performance, Driving, Organization.